Graphene-Based Absorber: Tunable, Highly Sensitive, Six-Frequency - Xinmei Wang; Xianding He; Hua Yang; Xu Bao; Yongjian Tang; Pinghui Wu; Yougen Yi (Molecules)
Due to the equipartition exciton property of graphene metamaterials, researchers have applied them to the design of absorbers and developed a series of absorbers covering different wavebands (including narrowband and broadband). In this paper, an absorber based on surface-isotropic excitations was designed with the help of graphene metamaterials and relevant simulations. The absorber exhibited six perfect absorption peaks in the mid-infrared band and had an extremely simple structure consisting of only three layers: a gold layer at the bottom, a dielectric layer made of silica in the middle, and patterned graphene at the top. This absorber possesses excellent tuning ability, and by applying an external bias to the graphene layer, the Fermi energy level of graphene can be adjusted, and thus the resonance frequency of the absorption peak can be tuned. Meanwhile, the effect of the graphene relaxation time on the absorber performance was investigated. In addition, the refractive index of the dielectric layer was found to be linearly related to the resonance frequency of the absorption peak. It is worth mentioning that the absorber structure possessed polarization insensitivity due to its central symmetry. Even when incident light with different polarizations was incident over a wide range of angles, the change in absorbance of the absorption peaks was negligible, demonstrating significant insensitivity to the angle of incidence. The sensor possesses excellent characteristics such as tunability, polarization insensitivity, incident angle insensitivity, and high sensitivity. This paper demonstrates the feasibility of a six-frequency sensor and opens up more ideas for the design of multi-frequency sensors.